2022
DOI: 10.55299/ijec.v1i2.274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interpersonal Relationships on Job Satisfaction Through Organizational Culture at the Camat Office, Samalanga District, Bireuen Regency

Abstract: The Samalanga sub-district office is one of the sub-district offices in Bireuen Regency, which is the operational activity needs competent workers, therefore the management of human resources should also be improved. In this case the interaction between superiors and subordinates and employees with employees must be well established. When the interpersonal relationship in the work environment has been applied so that in the company or agency will create an organizational culture that will differentiate the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This finding was supported by Oyovwe-Tinuoye ( 2020) who conducted a study on the relationship between interpersonal relations and job satisfaction of librarians in the university libraries in Southern Nigeria and found that a significant relationship existed between interpersonal relations and job satisfaction of librarians in university libraries in Southern Nigeria. However, the finding of this study is at variance with Zuhra (2022) who conducted a study on the effect of interpersonal relationships on job satisfaction through organizational culture at the Camat Office, Samalanga District, Bireuen Regency and found that interpersonal Relationship has no direct effect on Job Satisfaction Through Organizational Culture…”
Section: Discussion Of Findingscontrasting
confidence: 88%
“…This finding was supported by Oyovwe-Tinuoye ( 2020) who conducted a study on the relationship between interpersonal relations and job satisfaction of librarians in the university libraries in Southern Nigeria and found that a significant relationship existed between interpersonal relations and job satisfaction of librarians in university libraries in Southern Nigeria. However, the finding of this study is at variance with Zuhra (2022) who conducted a study on the effect of interpersonal relationships on job satisfaction through organizational culture at the Camat Office, Samalanga District, Bireuen Regency and found that interpersonal Relationship has no direct effect on Job Satisfaction Through Organizational Culture…”
Section: Discussion Of Findingscontrasting
confidence: 88%